2012
DOI: 10.1517/13543776.2012.727397
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoline derivatives: a patent review (2006 – present)

Abstract: With the uncovering of the molecular mechanisms related to neurodegenerative diseases and cancer, the use of classical and novel imidazoline structures has been more frequently noted in recent (2006 - 2012) patented agents for the treatment of neurodegenerative diseases and cancer instead of agents for the treatment of cardiovascular disease noticed earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…68 It can be observed that for both EIS and the PDP data, the slope and the regression coefficient are close to unity, which supports the validity of the Langmuir isotherm. The K ads was used to calculate the standard free energy of adsorption (ΔG ads 0 ): 69,70 5 ) ads 0 ads (7) where the symbols R and T have their usual meaning, and the value 55.5 provides the molar concentration of water. The calculated ΔG ads 0 values from the EIS and PDP data are −31.78 and −32.06 kJ mol −1 , respectively, showing that the adsorption of the inhibitor molecules on the steel substrate obeys a mixed mode of physical and chemical adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 It can be observed that for both EIS and the PDP data, the slope and the regression coefficient are close to unity, which supports the validity of the Langmuir isotherm. The K ads was used to calculate the standard free energy of adsorption (ΔG ads 0 ): 69,70 5 ) ads 0 ads (7) where the symbols R and T have their usual meaning, and the value 55.5 provides the molar concentration of water. The calculated ΔG ads 0 values from the EIS and PDP data are −31.78 and −32.06 kJ mol −1 , respectively, showing that the adsorption of the inhibitor molecules on the steel substrate obeys a mixed mode of physical and chemical adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…To counter this issue, a number of organic compounds are introduced as additives in the corrosive solution to minimize the damage caused to the steel structures. Most of the research and development in the area of sweet corrosion inhibitors have been reported on the use of imidazoline-based corrosion inhibitors. , It should be noticed that these molecules require a tedious synthesis procedure, are expensive, and are highly toxic. Therefore, considering the environmental constraints, there is a lot of research work currently undergoing in the area of environment-friendly corrosion inhibitors. , …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these studies helped establishing that changing N 1 side chain interferes mainly with PK properties but also with potency [ 62 , 63 ]. Several other analogs are disclosed in patents from Hoffman-La Roche, presenting the same imidazoline core and other structure variations such as imidazopyridinones [ 30 , 39 , 64 , 65 ]. Moreover, Miyazaki et al .…”
Section: Reactivation Of P53 As a Therapeutic Strategymentioning
confidence: 99%
“…2-imidazolines are a class of important heterocyclic compounds due to their potent biological activity and surfactant property. [10,11] Among various 2-imidazolines, hydroxy-functionalized 2-imidazoline is of particular appeal, as the extra hydroxy functional group renders it particularly useful for the synthesis of many physiologically active compounds, such as RX 781094, cirazoline and phentolamine as adrenergic antagonists [Scheme 1, (3)]. [12,13] The conventional manufacture of 2-imidazoline mainly relies on the condensation of ethylenediamine (EDA) with costly pre-functionalized fossil-based chemicals, such as nitriles and esters, which usually involve several synthetic steps from fossil fuel [Scheme 1, (1)].…”
Section: Introductionmentioning
confidence: 99%